2017
DOI: 10.1590/1678-77572016-0094
|View full text |Cite
|
Sign up to set email alerts
|

Repair of bone defects using adipose-derived stem cells combined with alpha-tricalcium phosphate and gelatin sponge scaffolds in a rat model

Abstract: Objectives This study aimed to evaluate the potential of adipose-derived stem cells (ASCs) combined with a modified α-tricalcium phosphate (α-TCP) or gelatin sponge (GS) scaffolds for bone healing in a rat model.Material and Methods Bone defects were surgically created in the femur of adult SHR rats and filled with the scaffolds, empty or combined with ASCs. The results were analyzed by histology and histomorphometry on days seven, 14, 30, and 60.Results Significantly increased bone repair was observed on days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…As for the osteodifferentiation capability of the two cell types, both promoted the formation of mineralized tissue in vitro, although the level of expression of osteocalcin was higher in the BFPSCs. This is consistent with the accumulating evidence supporting the usage of DPSCs [ 31 , 32 , 33 , 34 , 35 ] and ASCs [ 36 , 37 , 38 , 39 , 40 ] as promising tools for bone regeneration.…”
Section: Discussionsupporting
confidence: 91%
“…As for the osteodifferentiation capability of the two cell types, both promoted the formation of mineralized tissue in vitro, although the level of expression of osteocalcin was higher in the BFPSCs. This is consistent with the accumulating evidence supporting the usage of DPSCs [ 31 , 32 , 33 , 34 , 35 ] and ASCs [ 36 , 37 , 38 , 39 , 40 ] as promising tools for bone regeneration.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, in animals of the study group, the newly formed bone trabeculae were more mature and more efficiently filled the defect area (100.0 vs 60% in control) (see Figure 8 (b) ). The present histological results are, to some extent, comparable with reports by others, although those were mostly related to acute aseptic experiments [ 13 , 16 , 17 , 24 , 26 ].…”
Section: Resultssupporting
confidence: 93%
“…The availability and relative abundance of adipose tissue MSCs, in contrast to bone marrow cells, promotes an increasing interest in their clinical application as a source of cellular material for bone regeneration [ 14 , 15 ]. In animal studies, sizable restoration of bone tissue from adipose tissue MSCs has been demonstrated [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, polysaccharides too like chitosan [112114] or cornstarch [65, 115] have been investigated for this purpose. In between the animal-derived polymers, ASCs have demonstrated to positively interact mainly with fibrin [116], collagen [117, 118], gelatin [111, 119, 120], and silk [69, 121, 122], through the recognition of specific domains present in polymers' structures. These polymers have a good biodegradability profile, and they can be degraded, modified, or adsorbed by the action of naturally occurring enzymes [123].…”
Section: Scaffolds and Adipose Stem Cellsmentioning
confidence: 99%